Packing problems and project scheduling models: An integrated perspective - Sönke Hartmann (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1999)
This paper considers two problem classes that are important to researchers as well as practitioners, namely packing and project scheduling problems. First, the two problem categories are described. This includes a classification of packing problems as well as of project scheduling concepts. While both problem classes are different with respect to their fields of application, similarities of their mathematical structures are examined. It is shown that all packing problems considered here are special cases of models for project scheduling. The aim is to indicate which project scheduling models can be used to capture the different types of packing problems. Finally, some implications for research on optimization algorithms for these two problem classes are discussed.
Keywords: 650; Packing; Logistics; Project Management; Scheduling; Modeling; Verpackung; Projektmanagement; Scheduling-Verfahren; Packproblem; Theorie